1997
DOI: 10.1007/s002280050317
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamic effects of the angiotensin II antagonist valsartan at steady state in healthy, normotensive subjects

Abstract: Pharmacokinetics of valsartan are unchanged after multiple once-daily dosing, with little (expected) accumulation in plasma. Effects of 200 mg valsartan on blood pressure in healthy subjects on a normal sodium intake are small and become more prominent after repeated dosing. Indirect evidence of AT1 blockade by valsartan is demonstrated by an increase of plasma Ang II and by a blunted DBP response to passive tilting. The decrease in blood pressure at steady state enhances the increase in plasma Ang II. Valsart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 17 publications
6
47
2
Order By: Relevance
“…The study has also shown that treatment of normal volunteers with valsartan only, did not affect BP and PWV under standardised conditions, which is in contrast to that reported by Muller et al 15 They treated 16 healthy volunteers with valsartan (200 mg) for 8 days and showed a significant fall in SBP and DBP. The difference in effect of valsartan between the two studies could reflect a different salt intake by the respective volunteers, however racial differences in response to the drug 16 cannot yet be excluded.…”
Section: Discussioncontrasting
confidence: 66%
“…The study has also shown that treatment of normal volunteers with valsartan only, did not affect BP and PWV under standardised conditions, which is in contrast to that reported by Muller et al 15 They treated 16 healthy volunteers with valsartan (200 mg) for 8 days and showed a significant fall in SBP and DBP. The difference in effect of valsartan between the two studies could reflect a different salt intake by the respective volunteers, however racial differences in response to the drug 16 cannot yet be excluded.…”
Section: Discussioncontrasting
confidence: 66%
“…8 Protein binding of valsartan is high (94 -97%, mainly to albumin), 14,15,147 and its Vd is 17 L. 14,15,145 The Cl T of valsartan is 37 mL/min (Table 6b), and plasma elimination t . is in the range of 6-10 h. 14,15,[144][145][146]148 The drug does not accumulate significantly (Ͻ20%) after repeated dosing. 8,14,15 Valsartan is eliminated mainly by biliary excretion as unchanged drug in faeces (Table 7; 80-85%).…”
Section: S79mentioning
confidence: 99%
“…8,14,15,144,145 Oral bioavailability (Table 6a) is about 19% (range 10-35%) if given as a capsule, but 39-51% if given as a solution. 8,14,15,145,146 The T max of valsartan is 2-4 h after the administration of a capsule; 8,14,15 the absorption is more rapid if the drug is given as a solution (T max = 1 h). 145 Food decreases C max by 50% and AUC by 40%.…”
Section: S79mentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC with UV detectors are easy to handle. The HPLC methods with photodiode array (PDA) and UV detectors have also been reported for the extraction of valsartan from the human plasma [1,18,19] .…”
Section: Several Bioanalytical Methods Have Been Reportedmentioning
confidence: 99%